A Comparative Study of Scholarship and Non Scholarship Recipient Students on Learning Achievement at Madako University Tolitoli - Novianti; Ismail Yunus H; Moh. Firmansyah (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2024)
: The purpose of this study was to determine the significant differences in learning achievement between scholarship and non-scholarship students at Madako University of Tolitoli, Faculty of Teacher Training and Education, Department of English Education. This study used quantitative methods The instrument in this study was documentation. The researcher used IBM SPSS program to analyze the data. The results of this study showed that the average score obtained by scholarship recipient students reached a score of 3.74, while non-scholarship recipient students obtained an average score of 3.73. Normality test with significant test results for scholarship students is 0.023 <0.05 and normality test with significant test results for non-scholarship students is 0.003 <0.05, so the data is not normally distributed. The results of the Whitney u test mean difference test were significant 0.279> 0.05 so that it was stated that the Ho hypothesis was accepted, and Ha was rejected, so the study concluded that there was no significant difference between scholarship and non-scholarship students.